Assessing the Impact of Counseling Interventions on Student Academic Outcomes in Secondary Schools: An Experimental Study - Akhtar, Samina; Ali, Romina; Shakir, Muhammad Saeed (Annals of Human and Social Sciences, 2024)
The main purpose of the current experimental research was to analyze the impact of counseling on underachieving students by the head teachers at the secondary level. The study's population comprised 219 students from the 9th and 10th classes at City School, a private school located in the district of Multan, Punjab, Pakistan. The study's total sample size was 91, including both male and female students from Classes 9th and 10th. The researchers used 24 students as an experimental group and 24 students as a control group. The researcher analyzed the data by calculating the percentages and mean scores. The scholar administered a pre-test to diagnose the underachieving students. The findings revealed that counseling had significantly improved the academic performance of underachieving students. The study recommended initiating counseling programs that address both academic challenges and the need to create a holistic support system for students in schools.